2005
DOI: 10.1143/jjap.44.2509
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large-Area GaN-Based Light-Emitting Diodes on Cu Substrate

Abstract: A large-area GaN-based light-emitting diode (LED) 1000×1000 µm2 in size with a p-side down configuration was fabricated using wafer bonding and laser lift-off (LLO) techniques. The thin GaN LED was transferred onto a copper substrate without peeling or cracks. The large-area LEDs showed a uniform light-emission pattern over entire defined mesa area without a transparent contact layer on the p-type GaN. The operating current of the large-area LEDs can be driven up to 1000 mA with continuously increasing light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Robidas et al [13] reported improvement in light extraction efficiency in case of planar LEDs using patterning. At operation voltage, better current spreading, better heat dissipation capability, better light extraction, higher driving current density, flexible chip size scaling and good reliability [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Robidas et al [13] reported improvement in light extraction efficiency in case of planar LEDs using patterning. At operation voltage, better current spreading, better heat dissipation capability, better light extraction, higher driving current density, flexible chip size scaling and good reliability [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Other than the fundamental droop issue, recently, laser lift-off (LLO) LEDs were demonstrated to eliminate the bad thermal dissipation of sapphire. Some scholars are using very high thermal conductivity material to solve this problem, such as electroplated copper (400 W/k-m) or metal base substrate [ 11 , 12 ]. Because of difficulties in metal cutting, silicon substrate becomes an alternative to replace sapphire substrate as well [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non‐uniform three‐dimensional (3D) current distribution especially in the p ‐ type contact layers of the LEDs could result in serious problems such as local heat generation, early saturation of light emission intensity, and filamentation as well as shortened device lifetime 17–19. Therefore, it is essential to attain contacts to p ‐ type GaN for excellent current spreading with negligible current crowding to achieve reliable operation.…”
Section: Introductionmentioning
confidence: 99%